2021
DOI: 10.1016/j.snb.2021.130242
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed colorimetric detection of SARS-CoV-2 and other pathogens in wastewater on a 3D printed integrated microfluidic chip

Abstract: Graphical abstract A sensitive multiplexed colorimetric analysis platform for the detection of SARS-CoV-2 and human enteric pathogens in wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 49 publications
(58 reference statements)
0
40
0
Order By: Relevance
“…Yin et al developed a three-dimensional microfluidic chip with a two-stage amplification with the first incorporating recombinase polymerase amplification (RPA) and the second incorporating synergetic enhanced colorimetric, loop-mediated isothermal amplification (SEC-LAMP). The colorimetric signal is read by the naked eye or a smartphone with a high sensitivity of 10 genome equivalent/mL within an hour ( Table 3 ) [ 109 ].…”
Section: Microfluidics In Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Yin et al developed a three-dimensional microfluidic chip with a two-stage amplification with the first incorporating recombinase polymerase amplification (RPA) and the second incorporating synergetic enhanced colorimetric, loop-mediated isothermal amplification (SEC-LAMP). The colorimetric signal is read by the naked eye or a smartphone with a high sensitivity of 10 genome equivalent/mL within an hour ( Table 3 ) [ 109 ].…”
Section: Microfluidics In Sars-cov-2mentioning
confidence: 99%
“…As for the material, PMMA was frequently used, followed by PDMS, polycarbonate, 192.24 IFC, nylon, glass, clear resin, and clear methacrylate-based resin [ 81 , 84 , 85 , 94 , 102 , 104 , 108 , 109 , 110 ]. Among fluid manipulation techniques, centrifugal force was the most commonly used strategy, followed by electrochemical pumping, capillary action, manual pipetting, hydrostatic pressure, isotachophoresis, and syringe pump [ 82 , 84 , 85 , 94 , 102 , 104 , 105 , 109 ]. Yang et al used manual pipetting followed by capillary action for the fluid manipulation strategy [ 107 ].…”
Section: Materials and Fluid Manipulation Techniquementioning
confidence: 99%
“…Liu et al developed a 3D printed microfluidic chip to detect the SARS-CoV-2 viruses using a Flinders membrane for nucleic acid extraction, recombinase polymerase amplification, and loop-mediated isothermal amplification for sensitive detection, a smartphone-based platform for colorimetric signal monitoring. The result showed that this microfluidic chip was able to detect SARS-CoV-2 as low as 100 GE/mL [ 98 ].…”
Section: Pathogen Detectionmentioning
confidence: 99%
“…The molecular diagnosis of characteristic nucleic acid of SARS-CoV-2 single-stranded positive-sense RNA genome swabbed from a patient's throat or nasal cavity has been adopted to achieve the early detection of the viral infection or contamination ( Chen et al, 2020 ; Wu, A. et al, 2020 ; Wu, F. et al, 2020 ), but the great challenge of early identification of COVID-19 is how to detect extremely trace amount of SARS-CoV-2 RNA from complex samples. Currently, the traditional detection methods are developed based on the enzyme-related nucleic acid amplifications such as polymerase chain reaction (PCR) ( Bienko et al, 2013 ; Chang et al, 2020 ; Corman et al, 2020 ; Karami et al, 2021 ; Markou et al, 2008 ; Sharfstein et al, 2020 ; Smyrlaki et al, 2020 ), loop-mediated isothermal amplification (LAMP) ( Nguyen and Lee, 2021 ; Yin et al, 2021 ; Zhu et al, 2020 ), and recombinase polymerase amplification (RPA) ( Cherkaoui et al, 2021 ; De Felice et al, 2022 ; Mancuso et al, 2021 ). Despite the great success of these techniques in trace viral nucleic acid testing, especially the PCR as the “gold standard” in SARS-CoV-2 diagnostics, there are still significant deficiencies or limitations in the requirements of precise primer design, enzyme activity-dependence, fine thermal control, and complex operations ( Liu, R. et al, 2020 ; Wang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%